Comparison of the efficacy of calcium versus acetaminophen on reduction of orthodontic pain - Soghra Yassaei; Alireza Vahidi; Farnaz Farahat (Wolters Kluwer Medknow Publications, 2012)
Background: Pain and discomfort are common during orthodontic treatment. Aim: The aim of this single blind clinical trial was to compare the effectiveness of oral calcium versus acetaminophen in pain reduction. Materials and Methods: In this study, the patients recorded their pain on a 100-mm visual analogue scale (VAS). Forty female patients (14-19 years old) who had passed at least 2 months of their first orthodontic archwire placement and their pain intensity was 40-100 mm (VAS) were selected and randomly assigned to two groups. Psychotic status was measured using Hospital Anxiety and Depression Scale (HADS). In group 1 calcium forte tablets (500 mg) and in group 2 acetaminophen (325 mg) tablets were prescribed to be taken one tablet per day. After consumption of all tablets (n=60), pain intensity was measured and compared with that before drug therapy. Results: The results indicated that the difference in pain intensity before and after drug administration in the calcium group was statistically significant (P<0.001), but not significant in the acetaminophen group (P=0.468). The difference between the pain reduction in the two groups were also statistically significant (P<0.001). In the calcium group 9.5% and in the acetaminophen group 15.8% had anxiety that was not statistically significant (P=0.631). In both groups, no subject had depression. Conclusion: Calcium is more effective than acetaminophen in long-term pain reduction during orthodontic treatment.